Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1128/aac.01111-17
|View full text |Cite
|
Sign up to set email alerts
|

When Good Bugs Go Bad: Epidemiology and Antimicrobial Resistance Profiles of Corynebacterium striatum, an Emerging Multidrug-Resistant, Opportunistic Pathogen

Abstract: Infections with have been described in the literature over the last 2 decades, with the majority being bacteremia, central line infections, and occasionally, endocarditis. In recent years, the frequency of infections appears to be increasing; a factor likely contributing to this is the increased ease and accuracy of the identification of spp., including, from clinical cultures. The objective of this study was to retrospectively characterize isolates recovered from specimens submitted as part of routine patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
90
2
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(107 citation statements)
references
References 35 publications
6
90
2
5
Order By: Relevance
“…Similarly, Mc Mullen et al [15] reported multiclonal spread among 85 C. striatum strains using rep-PCR, isolated between 2013 and 2015 in USA. Although half of the strains were in one group, the remaining strains were distributed into 11 different groups, and the strains in the dominant clone had different antibiotic resistance profiles.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Similarly, Mc Mullen et al [15] reported multiclonal spread among 85 C. striatum strains using rep-PCR, isolated between 2013 and 2015 in USA. Although half of the strains were in one group, the remaining strains were distributed into 11 different groups, and the strains in the dominant clone had different antibiotic resistance profiles.…”
Section: Discussionmentioning
confidence: 90%
“…In this study, all strains (100%) were resistant to tetracycline. Barberis et al [30] reported tetracycline resistance of 20% (11/55), whereas Wang et al [24] and Mc Mullen et al [15] reported as 58.3% (112/192) and 62% (128/206) respectively. It has also been reported that the tetA and tetB genes play a role in the tetracycline resistance of C. striatum strains and that the mechanism of resistance involves an active efflux pump [26,31].…”
Section: Discussionmentioning
confidence: 98%
“…C. striatum was reported to exhibit susceptibility to vancomycin, linezolid, and daptomycin; however, many isolates were reported to exhibit multidrug resistance. 2 Indications for pancreatic pseudocyst drainage include persistent pain attributable to the fluid collection, gastric or duodenal obstruction, biliary obstruction, development of pancreatic ascites or pleural effusion, pancreatic enlargement on serial imaging, and signs of pseudocyst infection or bleeding. 3 If the pseudocyst communicates with the main pancreatic duct, endoscopic transpapillary drainage with placement of a pancreatic duct stent is suggested.…”
Section: Discussionmentioning
confidence: 99%
“…3638 It is also being evaluated for efficacy and safety for the treatment of subjects with complicated S. aureus bacteremia and S. aureus right-sided infective endocarditis. 39 A recent study 40 suggests telavancin 4 may find utility in the treatment of the emerging multidrug-resistant pathogen Corynebacterium  striatum , and its effectiveness for eradicating biofilms in vitro and in vivo has been reviewed recently. 41 It is highly protein bound (∼93% in human plasma), 42 but the presence of albumin does not influence the in vitro antibacterial activity of telavancin to any great extent.…”
Section: Recently Approved Glycopeptidesmentioning
confidence: 99%